Hidden Chem Card to Improve Students’ Motivation and Learning Outcomes - Fatma, Anggun Zulfa; Lutfi, Achmad (FKIP Universitas Lampung, 2024)
Abstract: One of the causes of low student motivation is due to the lack of learning media support in learning activities. The purpose of this research is to obtain a hidden chem card game media that is feasible to increase students' motivation and learning outcomes in stoichiometry material. This research uses the type of Research & Development (R&D) research that was tested limited to 30 students grade 10 in senior high school. Data collection techniques used questionnaire method for students' response and motivation, observation method to observe students' activities, and test method for students' learning outcomes. The results showed that students' learning motivation increased, all statement items obtained high criteria, namely students' enthusiasm (increased by 12%), students' pleasure with chemistry subjects (increased by 9%), and a sense of wanting to study chemistry diligently (increased by 11%). The paired t-test results based on pretest-posttest scores showed a significant increase with the acquisition of moderate (44%) and high (23%) n-gain scores more than the low category (33%). This shows that the hidden chem card game media can increase students' motivation and learning outcomes. Keywords: hidden chem card, stoichiometry, learning motivation, learning outcomes. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp27-33